ACTUAL PROBLEMS OF NEWSPAPER HEADLINE RESEARCH THEORETICAL REQUIREMENTS FOR STUDYING ONLINE VERSIONS OF NEWSPAPERS - Turg’unova Fazilat Rustam qizi (Western European Studies, 2024)
This article examines the actual problems in researching newspaper headlines and the theoretical requirements for effective research into online newspapers. The rapidly evolving digital landscape has changed the way news is consumed, with a significant shift towards online newspapers. As a result, newspaper headline research has had to adapt to the demands of studying online versions
Keywords: Linguistic subsystem; national-cultural communities; newspaper headlines